Kinerja Organisasi dan Kelayakan Universitas Sulawesi Barat Menuju Status Perguruan Tinggi Negeri Berbadan Layanan Umum - Sitti Hadijah; Jumardi Jumardi; Muh. Yusran (Universitas Medan Area, 2023)
This article has two objectives, the first is to find out the organization's performance, and the second is the feasibility of West Sulawesi University becoming a State University with a Public Service Agency (BLU). The approach used in this research is descriptive qualitative research. Data collection techniques are through interviews, documentation, and observation. Data analysis techniques used in analyzing Organizational Performance and Feasibility to Become PTN BLU (Case Study of West Sulawesi University) There are several steps: data reduction, data presentation, and conclusion drawing. The results achieved are that the organizational performance of the University of West Sulawesi has not met the requirements to change status from working unit to BLU. The University of West Sulawesi is not yet able to implement a full public service agency management pattern where the requirements are substantive requirements, technical requirements, and administrative requirements must be met optimally, but Universitas Sulawesi Barat has gradually been fulfilled to become a BLU, where the reference is from the 3 existing requirements. Substantive and technical requirements have been fulfilled but administration has not been fulfilled.